Summer spatial variations in phytoplankton composition and biomass in surface waters of a warm-temperate, deep, oligo-holomictic lake: Lake Iseo, Italy - Leoni, B.; Marti, Clelia; Imberger, J.; Garibaldi, L. (2014)
© International Society of Limnology 2014. The spatial distribution of phytoplankton in the surface waters of a typical, deep subalpine lake was investigated by analysing water samples collected at 3 depth ranges (0-1, 9-13, and 15-19 m) at 7 sites (21 total samples) using a generalized linear model. The biovolume of different phytoplanktonic taxa significantly differed between depth ranges. Different algal taxa showed maximum population density at different depths as a result of different optima of light, physical conditions, and nutrients. The layer at 9-13 m depth showed the greatest abundance of phytoplankton, mainly represented by Bacillariophyceae and Cyanobacteria. Conversely, Chlorophyceae, which require few nutrients and are not inhibited by high light energy, were most abundant at the surface. The vertical heterogeneity in phytoplankton distribution closely paralleled that of nutrients, which in turn depend on the stable thermal stratification of the lake water column. Biovolume of phytoplankton taxa and chemical parameters did not differ significantly between sampling sites some kilometers apart due to large horizontal water movements in the lake that create relatively uniform conditions throughout the basin.